Robotic-assisted renal autotransplant as a novel treatment option for nutcracker syndrome. Issue 12 (24th December 2021) - Harkrader, Lacy; Alwatari, Yahya; Daisuke, Imai; Christanson, Johanna; Khan, Aamir; Bhati, Chandra
Abstract: Nutcracker syndrome can present with various disabling symptoms. To our knowledge, there are no reports that describe a robotic-assisted approach in its management. We present a patient who underwent robotic-assisted nephrectomy after the failure of conservative management of nutcracker syndrome and a second patient who underwent robotic-assisted nephrectomy with autotransplant. Surgery and immediate post-op courses were uncomplicated. Robotic-assisted nephrectomy with or without autotransplant can be a feasible, minimally invasive option for select patients with nutcracker syndrome.